2020
DOI: 10.1017/s1478951520000620
|View full text |Cite
|
Sign up to set email alerts
|

Assessing delirium with nursing care instruments: Evaluation of the cognitive and associated domains

Abstract: Objective Nursing instruments have the potential for daily screening of delirium; however, they have not yet been evaluated. Therefore, after assessing the functional domains of the electronic Patient Assessment — Acute Care (ePA-AC), this study evaluates the cognitive and associated domains. Methods In this prospective cohort study in the intensive care unit, 277 patients were assessed and 118 patients were delirious. The impacts of delirium on the cognitive domains, consciousness and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The incidence of delirium in the ICU was 10.13–78.46%, of which mechanically ventilated patients were the majority [ 25 , 26 ]. At present, there is still a lack of studies on the current status of delirium in patients with COPD and respiratory failure undergoing mechanical ventilation [ 27 ]. The results of this study have indicated that the incidence of delirium in patients with COPD combined with respiratory failure and mechanically ventilated is 21.94%, and for patients with age ≥ 75y, BMI ≤ 19 kg/m 2 , hypertension, APACHE II score ≥ 15, CPOT ≥ 5, sedation, PaO 2 ≤ 75 mmHg are the risk factors of delirium in elderly patients with COPD combined with respiratory failure undergoing mechanical ventilation, early targeted intervention and nursing care are needed for those patients to reduce the occurrence of delirium.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of delirium in the ICU was 10.13–78.46%, of which mechanically ventilated patients were the majority [ 25 , 26 ]. At present, there is still a lack of studies on the current status of delirium in patients with COPD and respiratory failure undergoing mechanical ventilation [ 27 ]. The results of this study have indicated that the incidence of delirium in patients with COPD combined with respiratory failure and mechanically ventilated is 21.94%, and for patients with age ≥ 75y, BMI ≤ 19 kg/m 2 , hypertension, APACHE II score ≥ 15, CPOT ≥ 5, sedation, PaO 2 ≤ 75 mmHg are the risk factors of delirium in elderly patients with COPD combined with respiratory failure undergoing mechanical ventilation, early targeted intervention and nursing care are needed for those patients to reduce the occurrence of delirium.…”
Section: Discussionmentioning
confidence: 99%